Strategies for Volumetric Recovery of Large Scale Damage in Polymers. (25th April 2016) - Krull, Brett P.; Gergely, Ryan C. R.; Santa Cruz, Windy A.; Fedonina, Yelizaveta I.; Patrick, Jason F.; White, Scott R.; Sottos, Nancy R.
Abstract : The maximum volume that can be restored after catastrophic damage in a newly developed regenerative polymer system is explored for various mixing, surface wetting, specimen configuration, and microvascular delivery conditions. A two‐stage healing agent is implemented to overcome limitations imposed by surface tension and gravity on liquid retention within a damage volume. The healing agent is formulated as a two‐part system in which the two reagent solutions are delivered to a through‐thickness, cylindrical defect geometry by parallel microvascular channels in thin epoxy sheets. Mixing occurs as the solutions enter the damage region, inducing gelation to initiate an accretive deposition process that enables large damage volume regeneration. The progression of the damage recovery process is tracked using optical and fluorescent imaging, and the mixing efficiency is analyzed. Complete recovery of gaps spanning 11.2 mm in diameter (98 mm 2 ) is achieved under optimal conditions. Abstract : The maximum volume recovery achievable by two‐stage healing chemistry is investigated for various mixing, surface wetting, specimen configuration, and microvascular delivery conditions . Gelation enables the healing agents to overcome the influence of gravity and surface tension to regenerate cylindrical damage volumes. Complete material recovery is achieved for damage regions ranging up to 11.2 mm in diameter, an increase of 197% over non‐gelling control fluids.